Anxiety and health related quality of life among obese women with type 2 diabetes mellitus - Thirumalai, Ranganathan; Shenoy, Vaisnaavi Venkat (International Journal of Research in Medical Sciences, 2018)
Background: T2DM is often accompanied by a marked reduction in QOL. Psychiatric comorbidity further worsens the QOL and is associated with poor glycaemic control and long term treatment outcomes in T2DM. Obesity may lead to anxiety disorders and is often associated with T2DM. Women in the general population are known to suffer from psychiatric problems more often than men. The health related QOL in a woman having T2DM and comorbid anxiety disorders is likely to be worse. We therefore analysed the QOL and anxiety symptomatology among obese women with T2DM. Methods: We conducted a cross-sectional study at the Government General Hospital, Chennai. We recruited 50 age and BMI matched obese women with and without T2DM. We also recruited 50 each of diabetic and non-diabetic non-obese women. We used the WHO QOL BREF to assess the QOL, HAM A to quantify anxiety and HAM D to assess depression. Results: A 71.5% of our patients experienced anxiety symptoms with scores on HAM A indicating mild to moderate levels of anxiety disorder. Obese patients irrespective of their glycaemic status had significantly higher levels of anxiety compared to our non-obese subjects. All our obese patients with T2DM scored statistically significant lowest means across all subdomains on the WHO QOL BREF scale. Obese subjects who had diabetes for >10 years were found to have severe anxiety disorder. The odds ratio that an obese woman would suffer from psychiatric comorbidity was found to be 10.211 (odds ratio = 10.211; 95% C.I. 2.963-35.185). Conclusions: Anxiety disorders are common in obese women having T2DM. They also had decreased physical health, social relation and psychological domain scores. Having diabetes mellitus for >10 years predicted anxiety symptoms among obese subjects. We suggest early diagnosis and prompt treatment of anxiety disorders in obese women with T2DM as part of their routine primary health care.